Wayward eaudiobook A novel. - Spiotta, Dana (Random House Audio, 2021)
A NEW YORK TIMES NOTABLE BOOK OF THE YEAR • A “furious and addictive new novel” ( The New York Times ) about mothers and daughters, and one woman's midlife reckoning as she flees her suburban life. “ A virtuosic, singular and very funny portrait of a woman seeking sanity and purpose in a world gone mad.” —The New York Times Book Review “Riddled with insights into aging, womanhood, and discontent, Wayward is as elegant as it is raw, and almost as funny as it is sad.” —Philadelphia Inquirer   “A comic, vital new novel.” — The New Yorker   Samantha Raymond's life has begun to come apart: her mother is ill, her teenage daughter is increasingly remote, and at fifty-two she finds herself staring into "the Mids" — that hour of supreme wakefulness between three and four in the morning in which women of a certain age suddenly find themselves contemplating motherhood, mortality, and, in this case, the state of our unraveling nation. When she falls in love with a beautiful, decrepit house in a hardscrabble neighborhood in Syracuse, she buys it on a whim and flees her suburban life — and her family — as she grapples with how to be a wife, a mother, and a daughter, in a country that is coming apart at the seams. Dana Spiotta's Wayward is a stunning novel about aging, about the female body, and about female complexity in contemporary America. Probing and provocative, brainy and sensual, it is a testament to our weird times, to reforms and resistance and utopian wishes, and to the beauty of ruins.